Thermally enhanced self-propelled droplet motion on gradient surfaces1. Issue 56 (19th June 2015) - Chakraborty, Monojit; Ghosh, Udita Uday; Chakraborty, Suman; DasGupta, Sunando
<x xml:space="preserve">Abstract</x> Enhanced droplet movement at elevated temperatures.